An assessment of the impact of the National Student Financial Aid Scheme (NSFAS) on Student Accommodation or Housing – Focus on the University of Pretoria (UP) - Fokala, Elvis (University of Pretoria, 2024)
Dissertation (LLM (Multidisciplinary Human Rights))--University of Pretoria, 2023.